In Vivo Evaluation of Superior Limbic Keratoconjunctivitis Using Laser Scanning Confocal Microscopy and Conjunctival Impression Cytology - Kojima, Takashi; Matsumoto, Yukihiro; Ibrahim, Osama M. A.; Sato, Enrique Adan; Dogru, Murat; Tsubota, Kazuo (Investigative Opthalmology & Visual Science, 2010)
To investigate the cytologic findings of superior bulbar conjunctiva in superior limbic keratoconjunctivitis (SLK) using laser scanning confocal microscopy and impression cytology in a prospective controlled study. Twenty-one eyes of 11 SLK patients (9 women, 2 men; mean age, 49.3 +/- 17.9 years) and 18 eyes of 9 control subjects (6 women, 3 men; mean age, 46.4 +/- 8.7 years) underwent tear function tests including vital stainings, Schirmer test, tear clearance test, digital confocal laser scanning microscopy, and conjunctival impression cytology. After confocal microscopy and impression cytology images were obtained, the mean individual epithelial cell area (MIECA), nucleocytoplasmic (N/C) ratio, and inflammatory cell density were analyzed. The correlation between confocal microscopy and impression cytology parameters was investigated. The MIECA of SLK patients and control subjects in confocal microscopy was 786.54 +/- 463.88 microm(2) and 311.50 +/- 78.30 microm(2), respectively. The mean N/C ratio was 0.356 +/- 0.090 and 0.490 +/- 0.038, respectively. The MIECA and N/C ratio in impression cytology showed significant correlation with the corresponding confocal microscopy parameters (MIECA, P = 0.0028; N/C, P = 0.0051). The inflammatory cell density in confocal microscopy significantly correlated with superior bulbar conjunctival Rose-Bengal scores (P = 0.0264). Laser scanning confocal microscopy seems to be an efficient noninvasive tool in the evaluation of phenotypic alterations of the conjunctival epithelium in SLK and may serve as an alternative for impression cytology. N/C ratio and inflammatory cell density appear to be two new promising parameters of in vivo confocal microscopy in the assessment of ocular surface disease in SLK.